Representasi Feminisme Dalam Film Captain Marvel - Dian Apriansyah (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2023)
This study aims to represent and find out how the signs of feminism described in the film Captain Marvel, the analysis used is semiotic analysis of John Fiske covering the level of reality, level of representation, and level of ideology. The film Captain Marvel tells about how a woman struggles for her rights from a series of actions to become a female super hero. The results showed the codes in Captain Marvel's film that the value of feminism is represented at the level of reality, namely the code of behavior, costume, appearance, manner of speech, makeup, movement, expression. The level of representation of the value of feminism is seen in character, camera, conflict, action, dialogue. Then at the level of ideology illustrated the value of feminism, especially the flow of liberal feminism because of the liberal feminism started from ourselves to get gender justice. After analyzing from each sequence category in the film Captain Marvel, the researcher draws the conclusion that feminism specifically discusses the struggle against discrimination through ways of appearing, carrying out actions, and resolving conflicts, which can be seen from codes at the level of reality, representation and ideology as contained in the theory of The Codes of Television by John Fiske.